ABOUT OPTIMIZING THE PHASE VELOCITY OF PROPAGATION OF WAVES IN THE TRANSPORT STREAM - Gasanov, Z. M. (Science and Transport Progress, 2006)
The article proposes an algorithm of solving the task of synthesis of optimum dependence of the excitations distribution phase speed on the density of vehicles in a transport stream. The methods of the theory of optimal control are used for the purpose.